Design and Develop Low-Cost Device on Monitoring Environmental Indoor Air Quality in Factory - Mohd Azrin, Mohd Said; Shawn Felix, Stephen; Nor Kamaliana, Khamis; Abdullah, Yassin; Ana Sakura, Zainal Abidin; Rudiyanto, Philman Jong; Mohamad Syazwan Zafwan, Suffian; Aishah, Arsad (RMP Publications, 2020)
Environmental indoor air quality is one of the major concerns in occupational safety and health issues related to workers.Nowadays,the evolvingof Internet of Things (IoT),the monitoring of the surrounding environmental desired parameters is more fascinatingwith the use of various sensors.Real time datanowcan be monitored with the Wi-Fi connection where the data being transfer across the network cloudwith different platform service. This research focusis on the environmental monitoring forindoor air qualityin terms of carbon monoxide (CO) in selected palm oil mill factory.This project aims to benefit the workersin a way where air quality is monitored. This low-cost deviceair quality monitoring (LCDAQM) usedan ESPduino-32 to collect and process sensed data to the ThingSpeak platform service that can be monitored through web based or apps. The level of the carbon monoxide(CO)willlight up the red LED when reach more than 50ppm which was set by OSHA. Result showsthat level of CO in factory is unhealthy and need future engineering control action. The validation between LCDAQMand RS CO metershow the percentage errorof 14.41%. Therefore, this study will help workers and factory to monitor and reduce theoccupationalsafety and health (OSH) related problems to indoor air quality in factory.